The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1051/e3sconf/202235501001
|View full text |Cite
|
Sign up to set email alerts
|

Trends in harnessing energy from waste biomass: pathways & future potential

Abstract: Demand for fuel energy is continually on the rise. There is also a constant challenge involved to ensure that all our energy needs are fulfilled. Persistent overconsumption of conventional fossil fuels due to the rise in global population aided by economic expansion has resulted in reduction of fossil fuel reserves. This has fuelled the need to boost research efforts on renewable and sustainable bioenergy feedstocks. Since bioenergy utilizes organic matter; therefore, it is an economically viable and clean sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These components are interconnected in a complex manner providing recalcitrance to the plant cell. The amount of these components varies in each plant [6]. Previous studies have already identified cellulose and hemicellulose to have the potential to be used as feedstock for energy production from biomass to produce bioethanol from it [7].…”
Section: Introductionmentioning
confidence: 99%
“…These components are interconnected in a complex manner providing recalcitrance to the plant cell. The amount of these components varies in each plant [6]. Previous studies have already identified cellulose and hemicellulose to have the potential to be used as feedstock for energy production from biomass to produce bioethanol from it [7].…”
Section: Introductionmentioning
confidence: 99%